Modernism, Postmodernism, and corporate power: historicizing the architectural typology of the corporate campus. Issue 2 (2nd April 2016) - Kerr, Ron; Robinson, Sarah K.; Elliott, Carole
Abstract: This paper explores the potential for a 'marriage' of history and critical organization studies through a conceptual synthesis of critical sociology and historiography and its application to a specific organizational phenomenon. It presents a case study of the architecture of the corporate campus headquarters, a type of business complex built in exurban, rural settings, focusing on a series of campuses built in the period 1945–2005. The main purpose of this research is to identify what the transition from architectural Modernism to Postmodernism tells us about the evolution of ideologies that animate corporations in relation to wider developments in capitalism. Our conceptual framework has temporal and spatial dimensions, drawing on architectural historiography and sociological concepts, thus allowing us to connect architecture and the social in relation to the production and projection of corporate power through a delimited historical period. We identify two main drivers behind the construction of the campuses: internally, to integrate the staff as a community, and externally, to project a desired corporate image. We also demonstrate how our conceptual synthesis sheds light on the rise and fall of individual corporations. We make the following contributions to management and organizational history: first, we demonstrate how studying organizations through the lens of corporate architecture helps us understand the connections between symbolic, social and physical space and forms of corporate power. Second, we show how a marriage of history and critical sociology can help us to understand how certain ideologically freighted architectural features endure – or return – within the changing configurations of capitalism and finally, methodologically, we demonstrate how historicizing architecture can shed light on the rise and fall of individual corporations within a given socio-historical context.